Financial Frictions and the Persistence of History: A Quantitative Exploration - Buera, Francisco J.; Shin, Yongseok (Journal of Political Economy, 2013)
We quantitatively analyze the role of financial frictions and resource misallocation in explaining development dynamics. Our model economy with financial frictions converges to the new steady state slowly after a reform triggers efficient reallocation of resources; the transition speed is half that of the conventional neoclassical model. Furthermore, in the model economy, investment rates and total factor productivity are initially low and increase over time. We present data from the so-called miracle economies on the evolution of macro aggregates, factor reallocation, and establishment size distribution that support the aggregate and micro-level implications of our theory.